Modal interpretations of quantum mechanics - Lombardi, Olimpia Iris (2017)
The original "modal interpretation" of non-relativistic quantum theory was born in the early 1970s, and at that time the phrase referred to a single interpretation. The phrase now encompasses a class of interpretations, and is better taken to refer to a general approach to the interpretation of quantum theory. We shall describe the history of modal interpretations,how the phrase has come to be used in this way, and the general program of (at least some of) those who advocate this approach.